SEG Technical Program Expanded Abstracts 2009 2009
DOI: 10.1190/1.3255145
|View full text |Cite
|
Sign up to set email alerts
|

Fault activation during hydraulic fracturing

Abstract: Microseismic monitoring was used to image hydraulic fracturing during a gas well stimulation. Some time after the end of the injection, there was an increase in the seismic deformation rate. Investigation of the frequency-magnitude characteristics during the pumping phase were consistent with other hydraulic fracture results, although the activity recorded after the end of pumping was more consistent with observations of natural seismic deformation along faults. The ratio of p-to s-wave amplitudes also varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 1 publication
3
29
0
2
Order By: Relevance
“…Overall, we find b = 2.17 ± 0.09 for average P-and S-wave magnitudes with a magnitude of completeness of 0.1. This is a very high b-value but similar to the values reported by other studies of fluid injection sites, for example during hydraulic fracturing (Maxwell et al, 2009) and at Enhanced Geothermal System (EGS) injections (Bachmann et al, 2012). However, looking at the data in more detail reveals that the b-value is dependent on the station-source azimuth, rather than the injection rate.…”
Section: Event Magnitudessupporting
confidence: 80%
“…Overall, we find b = 2.17 ± 0.09 for average P-and S-wave magnitudes with a magnitude of completeness of 0.1. This is a very high b-value but similar to the values reported by other studies of fluid injection sites, for example during hydraulic fracturing (Maxwell et al, 2009) and at Enhanced Geothermal System (EGS) injections (Bachmann et al, 2012). However, looking at the data in more detail reveals that the b-value is dependent on the station-source azimuth, rather than the injection rate.…”
Section: Event Magnitudessupporting
confidence: 80%
“…These have been reported to have been accompanied by a sharp reduction in b-value, calculated for a moving subset of events over the time that pumping took place (Maxwell et al, 2009 - Green et al, 2012). At the Preese Hall 1 well, 55 events were recorded.…”
Section: Earthquake Magnitudesmentioning
confidence: 98%
“…Moreover, Maxwell et al (2009) and Downie et al (2010) showed that the events recorded during hydraulic treatment have b-values close to 2, while the events associated with fault deformation have b-values close to 1. Analysis by Kratz et al (2013) on the microseismic events associated with 13 horizontal wells in the Barnett shale in North Texas shows that the b-value of fracture-related events is close to 2 whereas the b-value of fault-related events is close to 1.…”
Section: Discussionmentioning
confidence: 98%